METODE SIMULASI BERBASIS PROJECT BASED LEARNING SEBAGAI ALTERNATIF UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR KONSEP MUTASI PADA SISWA KELAS XII MIPA SMA NEGERI 1 MOGA TAHUN PELAJARAN 2019/2020 - Masruri Masruri (UIR Press, 2020)
Abstract Research aims to determine the increased motivation of learning and learning outcomes of biological mutation concepts in the students of Grade XII MIPA SMA Negeri 1 Moga through the implementation of simulation methods based on project-learning, as well as the constraints experienced in the learning process. The instrument used consists of a poll to learn the student's motivation, and the multiple choice tests (pre-test and post-test) are selected to know the student's learning outcomes. The Data in this study was analyzed qualitatively and quantatatives. Qualitative analysis is conducted to determine the motivation for learning, while quantitative analysis is used to determine the improvement of student learning outcomes in the mutation concept. After the authors process the learning using a project Based learning simulation method in class XII MIPA3 SMAN 1 Moga Year lesson 2019/2020 there is an increase in learning motivation and student learning outcomes. Through this learning activity students can calculate. Keywords: simulation methods, Project Based Learning, motivation, learning outcomes, mutation